Fostering the Ontological Turn. Gustav Bergmann (1906-1987) - Bonino, Guido (Philosophische Analyse / Philosophical Analysis, 2008)
Gustav Bergmann (1906-1987) was, arguably, one of the greatest ontologists of the twentieth century. In 2006 and 2007, after a period of relative neglect, international conferences devoted solely to Bergmann's work were held at the University of Iowa in the USA, Université de Provence in France, and Università degli Studi di Roma Tre in Italy. The fifteen papers collected in this volume were presented at the third of these conferences, in Rome, and are here divided into three sections: "Categories of a realistic ontology", "World, mind, and relations", "Metaphysics of space and time".